KONSTRUKSI PEMBERITAAN KONFLIK INDONESIA VS MALAYSIA DI SURAT KABAR ( - Qoniah Nur Wijayani; Netty Dyah Kurniasari; Tatag Handaka (Jurnal Komunikasi, 2012)
Confrontation between Indonesia and Malaysia frequently occurs. The conflicts between the two of nations then and now are always repeated and never go over. Since the Soekarno regime until Yudhoyono regime always comes up with several problems. On August 13, 2010, confrontation between Indonesia and Malaysia repeatedly happened. In the waters of Tanjung Berakit, Marine Police Malaysia (MPM) have arrested Indonesian officials (Kementerian Kelautan dan Perikanan (KKP)). Those reality has attracted a news media attentions for reporting. Jawa Pos and Kompas have performed Tanjung Berakit incident on the front pages for nearly a month. Both Jawa Pos and Kompas Kompas have published the reality in different perspective. Each of them constructs reality based on their views. Wanting to investigate the construction of news media above, this study uses framing theory to analyze the method of framing models Zongdang Pan and Gerald Kosicki M. It operationalizes the four dimensions of structural text news: syntax, script, thematic, and rhetorical. This study found that Jawa Pos constructs reality reporting on the arrest of three KKP officer by Marine Police Malaysia as a conflict between two countries that attacks each other. Both are enemies which opposites to each other. Malaysia has always been challenging Indonesia while Indonesia is not able to compensate. Disappointment refers to the Indonesian government. Jawa Pos thought that the settlement with take up arms can be done. Unlike The Jawa Pos case, Kompas constructs reporting on the arrest of three KKP officersis not a conflict between the two countries. It can be seen from the attitude of both countrie thatis very contradictory. If Indonesia is really angry with Malaysia, in reserve Malaysia is keeps in silent as if nothing happened. Even Malaysia considers that Indonesia is their friend. Kompas does not want to deteriorate their relationship. Indonesia and Malaysia are the two allied countries for mutual benefit. Kompas considers that Keeping a cool head may be the best solution for resolving the conflict. Maturity and politeness should be put forward.Keyword: Constructs, Indonesia vs Malaysia, Framing Analysis